KERUSAKAN LINGKUNGAN DAN JASA EKOSISTEM AKIBAT PERILAKU TEKANAN MANUSIA - Missleini Missleini (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
Humans and the environment are two words that cannot be separated. In fulfilling their needs, activities carried out by humans towards nature always cause damage to the environment itself. Therefore the management and protection of the environment must comply with environmental principles. The environment is part of the smallest ecosystems that always provide benefits to human life. The damage that occurs is in various environments or ecosystems, so that it will disrupt the components that make up an ecosystem such as diversity of varieties and diversity of species. Thus this will have an impact on the extinction of varieties or biological species in an ecosystem. each ecosystem responds to a disturbance, a disturbance that exceeds the resilience of an ecosystem, will produce dynamics that lead to the formation of ecosystem conditions that deviate from the previous ecosystem.